(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The structural aspect of prohibitive constructions in English and Uzbek languages is to be considered in this article. The author also discusses the formation of prohibition in both languages and compares them from a linguistic point of view. According to analyzes of paremiological units with prohibitions, it is clarified that in order to make the prohibitive forms English language we are required to focus on the order of words and additions in the sentences while in Uzbek language it is crucial to add some specific suffixes in a speech in order to form paremiological units.